KAJIAN SEMIOTIKA PIERCE PADA FOLKLOR BATU KUDA - Firmansyah, Arif; Mutmainnah, Rizqi Nur Hanifah; Ramadhan, Ardhia Khrsna (Magistra Andalusia: Jurnal Ilmu Sastra, 2024)
This study aims to obtain and describe the moral value of the oral tradition of Horse Stone folklore based on Pierce's semiotics in classifying objects based on the classification of symbols, icons, and indices. Pierce's use of semiotics is related to the uses possessed by folklore itself. All types of folklore, whether oral folklore, partly oral folklore or non-oral folklore, have uses or functions that are very important for human life.Â  This makes folklore in life can describe the way a person involves himself in the midst of community life. The method used qualitative method with a semiotic approach, because the results of data that have been generated and collected on the Horse Stone folklore will be described in the form of written data. Finally, the results of data processing are used as a proposal for literature teaching materials in high school based on the Independent Curriculum in the form of modules. Learning folklore or folklore has a very important role in efforts to preserve noble values and local cultural wisdom. In education, folklore can be used as a learning medium and can be used as learning material for students. The use of folklore as an educational medium can be utilized in various disciplines, which of course the selection of folklore used must be right with the subject matter to be delivered. The use of folklore as an educational medium also acts as one step in preserving existing local culture. Therefore, getting used to delivering lessons through teaching materials is an effort to preserve folklore as part of culture, both protection, utilization and development of folklore in the future.